trans-Dichloridobis[(6-nicotinoyl-2-pyridyl-κN6)(3-pyridyl-κN)methanone]copper(II) - Hong Qiang; Fan Zhang (Acta Crystallographica Section E, 2011)
In the title complex, [CuCl2(C17H11N3O2)2], the CuII ion is located on an inversion center. It exhibits a distorted octahedral coordination geometry defined by two chloride anions at trans sites and four 3-pyridyl N atoms at equatorial sites from two (6-nicotinoyl-2-pyridyl)(3-pyridyl)methanone ligands. The (6-nicotinoyl-2-pyridyl)(3-pyridyl)methanone ligand can be viewed as having two pendant 3-pyridyl rings attached to a central pyridyl skeleton via separate carbonyl bridges, acting in a κ2N,N′-chelating mode with its 3-pyridyl N atoms bound to the CuII ion. The pendant 3-pyridyl rings make a dihedral angle of 80.76 (5)°. In the crystal, molecules are linked through intermolecular C—H...π and C—H...O interactions, forming a three-dimentional framework.